2016
DOI: 10.1177/1932296816639315
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Technology Use and Efficacy in Type 1 Diabetes

Abstract: Since 1921 technology has existed to replace insulin and treat diabetes. Although a definitive link was established between HbA1c and complication risk over 20 years ago, 1 only a minority achieve HbA1c targets despite intensified insulin regimens and new technologies. 2 This narrative review focuses on how psychosocial functioning affects uptake and use of technologies and the impact of technology on psychosocial outcomes in adults and children with type 1 diabetes and their caregivers. It examines evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 119 publications
(219 reference statements)
0
46
0
10
Order By: Relevance
“…Previous research has identified significant socioeconomic inequalities in outcomes, self‐management practices, perceptions, technology provision and quality of care (Al Sayah et al . , Franklin , Naranjo et al . , Sortso et al .…”
Section: Case and Methodsmentioning
confidence: 99%
“…Previous research has identified significant socioeconomic inequalities in outcomes, self‐management practices, perceptions, technology provision and quality of care (Al Sayah et al . , Franklin , Naranjo et al . , Sortso et al .…”
Section: Case and Methodsmentioning
confidence: 99%
“…However, there may have been a regular care selection bias limiting the score range, in that personality characteristics thought to have a high potential for RT-CGM discontinuation could have been reason for diabetes teams to not consider RT-CGM. Alternatively, availability of specialized nurse practitioners for adjustments and trouble shooting and a clinical psychologist for psychological support may have facilitated continued use [25].…”
Section: Discussionmentioning
confidence: 99%
“…Motivated patients [59, 60] who have a positive outlook on the benefits of the AP with realistic expectations are good candidates for the AP [25, 29], because they will likely persevere when faced with hardships when adapting to the technology. While such patients could be favoured in AP allocation, these attitudes may also be fostered through patient coaching (see below).…”
Section: Domains Of Ethical Issuesmentioning
confidence: 99%